PENGARUH ARUS KAS OPERASI, ARUS KAS INVESTASI, ARUS KAS PENDANAAN, DAN LABA AKUNTANSI TERHADAP RETURN SAHAM - Ayulita Elisabeth (Journal of Accounting and Management, 2025)
The research conducted by the author aims to determine the effect of operating cash flow, investment cash flow, funding cash flow, and accounting earnings on stock returns. The population in this study were telecommunications companies listed on the Indonesia Stock Exchange. The sampling method is purposive sampling. The data used is secondary data obtained from the company's annual financial statements. Data management is done by statistical analysis method using SPSS software version 26 with several tests, namely descriptive analysis, multiple linear regression analysis, classical assumption test, and hypothesis testing.  The results of the study showed that partially operating cash flow has no significant effect on stock returns. Investment cash flow has a significant effect on stock returns. Funding cash flow has no significant effect on stock returns. Accounting profit has a significant effect on stock returns.